Deadline eaudiobook - Crutcher, Chris (Recorded Books Inc., 2008)
Winner of the Margaret A. Edwards Award for Outstanding Literature for Young Adults, Chris Crutcher is best known for his sports-related fiction. In Deadline, Ben Wolf learns that he has an incurable form of leukemia. Ben keeps the prognosis to himself, refusing treatment and deciding to live life for all it's worth. In the next year he plans to make the high school football team, date the girl of his dreams, and hassle his narrow-minded civics teacher whenever possible. But harboring his painful secret is harder than he imagined. "[T]eens' interest will be held by the story's dramatic premise."-Booklist